The hard problem makes the easy problems hard - a reply to Doerig et al. Issue 2 (3rd April 2021) - Pinto, Yair; Stein, Timo
ABSTRACT: In their paper Doerig et al. argue that we should put the hard problem aside and focus on empirical data to solve the 'easy' problems of consciousness – finding the neural and functional correlates of consciousness. In other words 'shut up and measure'. This has worked well with other thorny issues, such as explaining life, so why not adopt this approach here? We argue that despite the popularity of this view it is not feasible. In order to collect any consciousness data one needs to take an implicit or explicit stance on the hard problem.